2010
DOI: 10.4161/psb.5.10.13161
|View full text |Cite
|
Sign up to set email alerts
|

MOTHER OFFT ANDTFL1regulates seed germination and fertility relevant to the brassinosteroid signaling pathway

Abstract: B rassinosteroids (BRs) are a family of plant steroid hormones that play diverse roles in many aspects of plant growth and development. For example, BRs promote seed germination by counteracting the inhibitory effect of ABA and regulate plant reproductive development, thus affecting seed yield. We have recently reported that MOTHER OF FT AND TFL1 (MFT ) regulates seed germination through a negative feedback loop modulating ABA signaling in Arabidopsis. Here, we show that MFT function is also relevant to the BR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 11 publications
2
17
0
Order By: Relevance
“…In this study, we determined that KRP1 and KRP2 were preferentially induced by ABA and BR ( Figure 1C,D). Given that ABA and BR extensively regulate seed maturation and germination, as previously described [41][42][43][44][45][46], these results demonstrated that ABA and/or BR could affect the two cell cycle regulators by regulating cell proliferation during grain filling and seed germination processes.…”
Section: Discussionsupporting
confidence: 78%
“…In this study, we determined that KRP1 and KRP2 were preferentially induced by ABA and BR ( Figure 1C,D). Given that ABA and BR extensively regulate seed maturation and germination, as previously described [41][42][43][44][45][46], these results demonstrated that ABA and/or BR could affect the two cell cycle regulators by regulating cell proliferation during grain filling and seed germination processes.…”
Section: Discussionsupporting
confidence: 78%
“…MOTHER OF FT AND TFL1 ( MFT ) is an inducer of flowering in A. thaliana and acts redundantly with FT (Yoo et al ., ). MFT is also an inducer of germination in A. thaliana , mediating GA, ABA and BR crosstalk (Xi & Yu, ; Xi et al ., ). Homologs of this gene, however, are expressed in seeds in several species, and they act primarily as a germination regulator (Nishikawa et al ., ; Q. Li et al ., ; Tao et al ., ).…”
Section: Can Pleiotropy Be a Precursor To Divergence In Gene Functionmentioning
confidence: 99%
“…Exogenous BR application rescues the low germination phenotype of gibberellin mutants, and the seed germination of BR-related mutants is more sensitive to inhibition by abscisic acid (ABA) than the wild type (Steber and McCourt, 2001;Xue et al, 2009). Recent evidence suggests that the antagonistic effect of BRs on seed germination is partially mediated through the phosphatidylethanolamine binding protein MOTHER OF FT AND TFL1 (MFT) because application of BRs to loss-of-function mft mutants did not antagonize the inhibitory effect of ABA (Xi and Yu, 2010). The ABA inhibition of germination was overcome by overexpressing the Arabidopsis DWARF4 (DWF4) biosynthetic gene under the control of a seed-specific oleosin promoter in Arabidopsis .…”
Section: Plant Steroids and Vegetative Growth Seed Dormancy And Germimentioning
confidence: 99%